2004
DOI: 10.1055/s-2004-827231
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpene-Coumarin Ether and a New Abietane Diterpene and their Effects as Inhibitors of P-Glycoprotein

Abstract: A new sesquiterpene-coumarin ether (5'beta,9'alpha,10'alpha)-7-0-(3alpha-methoxy-8'(12')-drimen-11'-yl)-scopoletin, designated driportlandin (1) and a new abietane quinoid diterpene 16-hydroxy-abieta-8,12-diene-11,14-dione, named portlanquinol (2) together with lupeol, nepehinol, wrightial, formonetin and davidigenin were isolated and characterized from the Me2CO extract of whole dried plant of Euphorbia portlandica. The structures of the new compounds were elucidated from spectral data including 2D-NMR experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…The reversal of this resistance, via inhibition of drug efflux mechanisms, is a promising research area. In this regard, extensive studies have been performed in order to obtain new effective resistance modifiers from plants (11). The use of these natural bacterial resistance modifiers, including…”
Section: Galbanic Acid As An Inhibitor Of S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The reversal of this resistance, via inhibition of drug efflux mechanisms, is a promising research area. In this regard, extensive studies have been performed in order to obtain new effective resistance modifiers from plants (11). The use of these natural bacterial resistance modifiers, including…”
Section: Galbanic Acid As An Inhibitor Of S Aureusmentioning
confidence: 99%
“…1. B), a sesquiterpene coumarin ether compound, showed a significant effect in inhibiting the efflux pump activity mediated by pglycoprotein as compared with that of verapamil, a known resistance inhibitor (11). In the present study, we described the effect of galbanic acid, a major plant sesquiterpene coumarin present in Ferula szowitsiana on antimicrobial activity of antibiotics against S. aureus (18), as a modulator of antibiotic resistance on clinical isolates of S. aureus, and its possible inhibitory effect on MDR pumps.…”
Section: Galbanic Acid As An Inhibitor Of S Aureusmentioning
confidence: 99%
“…It has been shown that sesquiterpenes from the Celastraceae and Euphorbiaceae families could act as reversal agents (Spivey et al, 2002;Madureira et al, 2004). The probable mechanism of feselol action could be its interaction with and inhibition of the function of the MRP2.…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpene coumarins of the drimane type (diportlandin, conferone, mogoltacin, and feselol, Fig. 1) can increase the accumulation and effectiveness of several anticancer agents (Madureira et al, 2004;Barthomeuf et al, 2006;Neshati et al, 2009;Behnam Rassouli et al, 2009;Rassouli et al, 2011a;Mollazadeh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A new sesquiterpene-coumarin ether (5 0 b, Figure 4, Table 5) was isolated and characterized from the Me 2 CO extract of whole dried plant of Euphorbia portlandica 105 . Examined for its effects on the reversal of MDR on mouse lymphoma cells (L5178), sesquiterpene-coumarin ether proved to be more active than the verapamil.…”
Section: Coumarinsmentioning
confidence: 99%